Near-adult heights and adult height predictions using automated and conventional Greulich-Pyle bone age determinations in children with chronic endocrine diseases - Choukair, Daniela; Hückmann, Annette; Mittnacht, Janna; Breil, Thomas; Schenk, Jens-Peter; Alrajab, Abdulsattar; Uhlmann, Lorenz; Bettendorf, Markus (Indian journal of pediatrics, 2022)
To validate adult height predictions (BX) using automated and Greulich-Pyle bone age determinations in children with chronic endocrine diseases.
Online veröffentlicht: 1. Februar 2022
Gesehen am 19.07.2023